Recent Advances in the Application of Ring-Closing Metathesis for the Synthesis of Unsaturated Nitrogen Heterocycles - Groso, Emilia J.; Schindler, Corinna S. (Synthesis, 2019)
This short review summarizes recent advances relating to the application of ring-closing olefin-olefin and carbonyl-olefin metathesis reactions towards the synthesis of unsaturated five- and six-membered nitrogen heterocycles. These developments include catalyst modifications and reaction designs that will enable access to more complex nitrogen heterocycles.1 Introduction2 Expansion of Ring-Closing Metathesis Methods3 Evaluation of Catalyst Design4 Indenylidene Catalysts5 Unsymmetrical N-Heterocyclic Carbene Ligands6 Carbonyl-Olefin Metathesis7 Conclusions
Keywords: RCM; carbonyl-olefin metathesis; nitrogen heterocycles; catalyst design; ruthenium; Lewis acid catalysis